IMPLIKASI VIDEO GIZI PADA PELAJARAN PJOK TERHADAP PERUBAHAN KOGNITIF DAN AFEKTIF DALAM MENENTUKAN PEMILIHAN MAKANAN SEHAT - Iswahyudi; Sugiharto, Akip; Yayuk, Erna (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research aims to determine the implications of using nutrition videos in Physical Education, Sports, and Health (PJOK) subjects on changes in students' cognitive and affective aspects regarding healthy food choices. The background of this study lies in the importance of early nutrition education to encourage healthy and balanced food consumption behaviors. The research subjects were students from SMP Muhammadiyah 6 Wuluhan. Data collection instruments included learning video questionnaires, cognitive assessments, and affective attitude scales towards healthy food. The findings indicate that the use of nutrition videos in PJOK learning positively contributes to students' cognitive and affective changes. Therefore, the use of audiovisual media is recommended as an innovative learning strategy to support nutrition education in schools.